Introduction to feminist therapy : strategies for social and individual change - Evans, Kathy M. (SAGE, 2011)
An Introduction to Feminist Therapy, by Evans, Kinkade and Seem, focuses on the practical application of feminist theory to clinical experience. Whereas other books in the area tend to focus on specific clinical issues encountered by women (such as sexual abuse or rape), this book addresses a broad range of clinical situations. It offers strategies to be used by male or female therapists working with men, women, families, or groups. The primary goal of the book is to help instructors, students and professionals to learn 'how to' implement feminist therapy.